Who owns nature? About the rights of nature - Wesche, Tilo (Estudios de Filosofía, 2022)
Property rights are often seen as a gateway to the destruction of nature. In view of the ecological crisis, criticism of property rights is therefore becoming louder and louder. On the one hand, rightly so, since global warming, resource depletion, global pollution and the loss of species have been made possible by the private ownership of natural assets. On the other hand, the criticism falls short. Even common and public property does not protect natural assets from being overexploited, resources depleted, and values extracted. Moreover, it is questionable whether nature would actually be better off today without any property regulation. A new understanding of property that does justice to natural goods is therefore needed. The article considers the rights of nature as a way to rethink property in this sense and explores reasons to give rights of nature a general validity.